The Effectiveness of Social Support in Adolescents to Overcome Low Self-Esteem: Scoping Review - Kurniawan Kurniawan; Khoirunnisa Khoirunnisa; Casman Casman; Eriyono Budi Wijoyo; Atiq Rizka Azjunia; Euis Irna Nurpadillah; Gita Cahyani; Ilham Fajri; Lubna Najwa Wardani; Nisa Nizhan Nurfadillah; Rana Kumala; Windi Srirahayu; Yulia Agnia Nurrohmah (Fakultas Kedokteran, 2022)
Background: self-esteem is important and plays a vital role in the development of self-esteem during adolescence. Individuals with low self-esteem are characterized by a negative view of themselves and an avoidance focus to protect themselves from possible harm, whereas individuals with self-esteem have the motivation to maintain and increase self-esteem. Purpose: This study aims to determine the sources of support in adolescence and the relationship to the incidence of low self-esteem in adolescents. Methods: This study was a literature review, which searched data using dome databases, namely PubMed, Science Direct, and Google Scholar. Articles are then selected based on inclusion and exclusion criteria based on the PRISMA flow chart. Result: The findings were 18.467 articles, and 5 articles selected that met the criteria for this study. The data showed there is a strong relationship between social support and adolescent self-esteem, social support does affect the person's self-esteem in every way in a positive way. Conclusion: There are several kinds of social support obtained by teenagers from the surrounding environment as a form of self-esteem in adolescents including social support from teenagers' parents, friends, schools, teachers, and the surrounding community. Various forms of support that adolescents get such as emotional support and instrumental support.Keywords: adolescence; self-esteem; social support